Shining a Light on Spectrophotometry in Bacteriology - Veronica Montesinos-Cruz; Greg A. Somerville (Antibiotics)
Spectrophotometry is widely used in biological sciences. In bacteriology, spectrophotometric monitoring of cell numbers during cultivation provides a rapid assessment of growth. Unfortunately, familiarity with this technique has led scientists to become complacent in its usage. Here, we review some guiding principles of spectrophotometry and practical considerations that may influence the outcome of experiments. This perspective is intended to assist both new and seasoned scientists in presenting robust and reproducible growth data based on spectrophotometric readings.